List of Members, Associates and Junior Associates ?Geographical (3a9493a3-083d-47f1-9c9d-039358d2a227) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
ALABAMA Aldrich.-Lloyd, T W Anniston.-Carrington, F G Gerber, A B Heimrod, A A. White, H E Ashland.-Barton, J C Sturdevant, J C Bessemer.-Abbott, C E Ball, T L Hines, H K Hodgkin, W -0. Salmon, H S Thompson, N E Birmingham.-Adams, J H Adler, J. E Aldrich, T H Aldrich, T H, Jr. Ball, E M